Photoluminescence and damage recovery studies in Fe-implanted ZnO single crystals - Monteiro, T. (2012)
We report Fe3+-related emission in ion-implanted ZnO single crystals. Iron ions were implanted at room temperature with 100 keV and a fluence of 1×1016 Fe+/cm2, and were submitted to annealing treatments in vacuum and in air. After implantation, the damage raises the minimum yield (χmin) from 2% to 50%. Annealing in an oxidizing atmosphere leads to a reduction of the implantation damage, which is fully recovered after annealing at 1050 °C with a χmin∼3% in the implanted region. With extrinsic excitation, red Fe-related emission is observed at low temperatures. The intensity is dependent on the annealing conditions. For samples annealed in air, the luminescence can be detected up to 120 K. When a comparison is made between unimplanted and post-implanted annealed samples, noticeable changes on near-band-edge and deep-level photoluminescence spectra are observed. A thermally populated structured green emission could be observed in the sample annealed in air, as shown by the temperature-dependent photoluminescence excitation studies.